The Planned Happenstance Career Inventory: A Cross‐Cultural Comparison. Issue 4 (1st December 2019) - Lee, Ji Hae; Cho, Soohyun; Lee, Sujung; Lee, Sang Min
Abstract : This study examined the measurement invariance and latent mean difference of an English version (J. H. Lee et al., 2017) of the Planned Happenstance Career Inventory (PHCI; B. Kim, Jung, et al., 2014) across cultures. Participants were 262 American and 291 South Korean undergraduates. Measurement invariance results indicated that the 5‐factor structure was adequate for both groups and that conditions for configural, metric, and partial intercept invariance were met. Latent mean analysis was used to compare the mean scores of the PHCI skills (curiosity, flexibility, persistence, optimism, and risk taking). The latent means of curiosity, flexibility, persistence, and optimism were higher among South Korean undergraduates, but no significant difference was found regarding risk taking. Career counselors should consider differences in planned happenstance perceptions across cultures to provide better career guidance. Future studies are needed to verify the distinctive nature of flexibility by replicating the factor structure of the PHCI with other samples.